Hill, Skill, and Will: Dyscalculia and Executive Functioning: Understanding Dyscalculia and its Impact on Executive Functioning and Child Development (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the present educational dynamics various neurological, cognitive, developmental and psychological approaches coexist. Child development and the related anomalies (Developmental Disorders) to developmental mindset have been a matter of both interest and research.One such DD is Mathematical Learning Disability or Dyscalculia. Dyscalculia is that condition which makes the acquisition of numeracy skills, one of the component skill of life difficult. Thus not only hampering their mathematics achievement but also it leads to a demotivating decomposition. This paper endeavours to make this ‘invisible disability’ visible and acknowledge the need to see a bigger picture. The paper further aims to study Dyscalculia and Executive functioning (EF) and study EF in the developmental perspective and construe as the integration of three parameters (“Hill, Skill Will”) in the long run to accommodate to a better inclusivity and enhanced living experiences.